2013
DOI: 10.5812/jjm.4896
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Pattern of Methicillin Resistant and Methicillin Sensitive Staphylococcus aureus Isolates in Tehran, Iran

Abstract: A B S T R A C TBackground: Staphylococcus aureus is associated with different infections ranging from skin and soft tissue infections to endocarditis and fatal pneumonia. S. aureus is still the most common bacterial species isolated from inpatient specimens and the second most common from outpatient specimens. Today, methicillin resistant S. aureus (MRSA) isolates are present in the hospitals of most countries and are often resistant to several antibiotics. Objectives: This study was conducted from 2007 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
35
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 23 publications
(28 reference statements)
11
35
2
Order By: Relevance
“…The prevalence of erythromycin-resistant strains was significantly lower in other studies (30)(31)(32). On the other hand, we found that 10 biofilm and non-biofilm-producing strains showed susceptibility to all tested antibiotics except for penicillin; these findings are consistent with our previous reports for S. aureus strains (17,(33)(34)(35)(36)(37)(38). Moreover, resistance of biofilmproducing strains to 13 tested antibiotics in this study highlighted the important role of these strains to cause severe infections, which do not respond to broad spectrum of antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of erythromycin-resistant strains was significantly lower in other studies (30)(31)(32). On the other hand, we found that 10 biofilm and non-biofilm-producing strains showed susceptibility to all tested antibiotics except for penicillin; these findings are consistent with our previous reports for S. aureus strains (17,(33)(34)(35)(36)(37)(38). Moreover, resistance of biofilmproducing strains to 13 tested antibiotics in this study highlighted the important role of these strains to cause severe infections, which do not respond to broad spectrum of antibiotics.…”
Section: Discussionsupporting
confidence: 92%
“…In other studies from Iran, the prevalence of penicillin resistance among MRSA isolates was 100% (10,(26)(27)(28)30). Possibly, the general use of ampicillin for the treatment of infections in poultry may explain this finding.…”
Section: Discussionmentioning
confidence: 78%
“…The occurrence of erythromycin resistance among poultry MRSA was significantly lower than that observed among MRSA of human origin, in Iran (10,(26)(27)(28)(29). Macrolides are not normally used for therapy of infections in poultry in Denmark, whereas the frequent occurrence of macrolide resistance might reflect the use of the spiramycin, as a growth promoter of poultry, in Iran.…”
Section: Discussionmentioning
confidence: 90%
“…In a study conducted on 726 S. aureus isolates (2007 to 2011) from 3 referral hospitals in Tehran (Iran), 30% of strains were found to be MRSA and mec A gene was detected among all MRSA isolates. No strains were resistant to vancomycin, synercid, linezolid, and chloramphenicol (5). In a random sample population from 4 hospitals including various clinical samples in Tabriz from year 2005 to 2012, 151 Staphylococcus aureus isolates were separated and meca gene, representative of MRSA was found in 35%, and 95% were resistant to penicillin and all isolates were susceptible to vancomycin and teicoplanin yet 5.9% were resistant to linezolid (6).…”
Section: Dear Editormentioning
confidence: 99%
“…There are very few reports of vancomycin and linezolid resistant MRSA in Iran (4,5,17); Fathollahzadeh (2004 to 2005; Tehran) reported that 99 out of 277 (36%) hospitaladmitted wound or blood specimens were MRSA Staphylococcus aureus isolates. All were susceptible to vancomycin, teicoplanin, linezolid, and tigecycline.…”
Section: Dear Editormentioning
confidence: 99%